How to design, optimise and implement a fibre-tip Fabry-Pérot cavity for quantum networks of atoms and photons - Mohammed, M (2021)
One of the most exciting prospects of quantum physics today is to simulate large quantum systems, intractable by classical computation, by connecting many smaller systems together. A cavity-based quantum network of atoms and photons constitutes one such approach, where each cavity interfaces between stationary atomic qubits in a node and photonic qubits travelling along optical fibre channels. For this scheme to work well, the cavity-based interface must be faithful and well-controlled.